Pengendalian Gulma Dengan Tanaman Sela Kacang Pada Budidaya Jagung Manis Tumpangsari - Setiawan, Agus Nugroho (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2005)
An research  on weed  control  with legumes  in sweet   corn intercropping   was conducted   in Kasihan, Bantul  District  of Yogyakarta  on February  to June 2003. The experiment  was aimed  to study  the role of legume  crop to control  weed growth  in  the intercropping    of sweet  corn. The experiment  was arranged in a single factor randomized  completely block  design (RCBD) with three blocks  as replication. The treatment  was the kind of legumes   i.e  groundnut, mungbean and soybean  planted  with sweetcorn  in the ratio of 1: 1, 1:2,  and 1:3 to be compared to  sole  crop of sweet  com  and legumes. The result  of this experiment showed that  legumes   existence reduced light  intensity   on soil surface. Presence of legumes as second crop with ratio up to 1:3 was significantly reduced  the weed growth  but not significantly influenced growth and yield of sweet corn. The higher the ratio of sweet  corn-legumes, the achievement of legumes yield  and land equivalent ratio were higher.